Evaluation of Vitek GNI+ and Becton Dickinson Microbiology Systems Crystal E/NF identification systems for identification of members of the family Enterobacteriaceae and other gram-negative, glucose-fermenting and non-glucose-fermenting bacilli. - O'Hara, C M (1997)
We evaluated the Vitek GNI+ and Becton Dickinson Crystal E/NF identification systems for their ability to accurately identify 619 and 626 strains, respectively, of members of the family Enterobacteriaceae and other glucose-fermenting and non-glucose-fermenting gram-negative rods. All strains tested were taken from a stock collection and passed three times on 5% sheep blood agar prior to testing. These strains represented a more rigorous challenge to both systems than one resulting from the testing of consecutive clinical isolates. Testing with both systems was done according to the manufacturers' instructions, and tests were repeated in duplicate when errors occurred. Vitek version 5.01 and Crystal version 3.0 softwares were used for identifications. The identification results from each system were compared with identifications previously determined with reference biochemicals. At the completion of the appropriate incubation period, the GNI+ and Crystal systems correctly identified 80.1 and 71.1% of the total isolates, respectively. After additional tests suggested by the software programs were completed, the GNI+ had an accuracy of 87.6% and the Crystal system's accuracy had improved to 87.9%. The error rates for the GNI+ and Crystal systems were 6.5 and 5.3%, respectively. A report of "no identification" was given for 6.0 and 6.9% of the isolates, respectively, and was associated with no particular organism group. One isolate each of Acinetobacter lwoffii and Vibrio alginolyticus would not grow in the Vitek card. The average times to detection for correct enteric identifications in the GNI+ system were 4.1 and 6.8 h for nonenteric identifications, while the Crystal results were routinely read at 18 h. We conclude that there was no significant difference (P > 0.05) between the results of the GNI+ card and those of the Crystal E/NF system after additional testing was performed with the group of organisms tested, but the overall accuracy for both systems in this study was below 90%.